2023
DOI: 10.1002/chem.202300169
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution of Calcite Grown in Zwitterionic Hydrogels: Charge Effects Enhanced by Gel‐Incorporation

Abstract: The incorporation of charged biomacromolecules is widely found in biomineralization. To investigate the significance of this biological strategy for mineralization control, gelatin-incorporated calcite crystals grown from gelatin hydrogels with different charge concentrations along the gel networks are examined. It is found that the bound charged groups on gelatin networks (amino cations, gelatin-NH 3 + and carboxylic anions, gelatin-COO À ) play crucial roles in controlling the single-crystallinity and the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Recently, the zwitterionic hydrogel (gelatin hydrogel) is used to further investigate the significance of gel-incorporation for crystal morphology control. [22] Differently, the charged groups (amino cations, gelatin-NH 3 + and carboxylic anions, gelatin-COO À ) are covalently bound on gel-fibers, which further enhances their charge effects on crystal morphology control. Therefore, in the further experiments, the gelatin-incorporated calcite crystals are prepared in gelatin hydrogels with different charge concentrations along gel-networks.…”
Section: Morphological Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the zwitterionic hydrogel (gelatin hydrogel) is used to further investigate the significance of gel-incorporation for crystal morphology control. [22] Differently, the charged groups (amino cations, gelatin-NH 3 + and carboxylic anions, gelatin-COO À ) are covalently bound on gel-fibers, which further enhances their charge effects on crystal morphology control. Therefore, in the further experiments, the gelatin-incorporated calcite crystals are prepared in gelatin hydrogels with different charge concentrations along gel-networks.…”
Section: Morphological Controlmentioning
confidence: 99%
“…Recently, the zwitterionic hydrogel (gelatin hydrogel) is used to further investigate the significance of gel‐incorporation for crystal morphology control [22] . Differently, the charged groups (amino cations, gelatin‐NH 3 + and carboxylic anions, gelatin‐COO − ) are covalently bound on gel‐fibers, which further enhances their charge effects on crystal morphology control.…”
Section: Morphological Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The cooperative effect of interactions between proteins and inorganic ions in biomineralization is being extensively investigated. Thus, it has been reported that the particular charge distribution in terms of concentration and distribution along the biomacromolecule may affect the orientation, polymorph and morphology of the biomineral [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%